The 2022 Criminal Code Revision: A Step Forward or a Backslide for Civil Liberties in Indonesia? (Indonesian Court and Justice Review, 2025)
The 2022 revision of Indonesia’s Criminal Code (KUHP) represents the most comprehensive overhaul of the country's penal law since independence. While proponents argue that the revision modernizes the legal system, critics have raised concerns over provisions that may curtail civil liberties, criminalize morality, and restrict freedom of expression. This study evaluates the implications of the new Criminal Code on fundamental rights, using a doctrinal approach supported by constitutional analysis and international human rights benchmarks. Key provisions analyzed include articles related to cohabitation, insults to the president, blasphemy, and protest regulation. Findings suggest that, despite attempts to harmonize customary norms and formal law, the Code introduces vague and overly broad clauses that could be misused to silence dissent and enforce moral conformity. Furthermore, the legislative process, marked by limited public consultation and swift ratification, raises questions about democratic legitimacy. The study argues that the 2022 revision reflects a broader trend of conservative legalism in Indonesia, where legal reform is used not to expand freedoms but to reinforce state control. The novelty lies in its comprehensive legal-constitutional analysis of the revised KUHP in light of democratic regression and civil rights. This research contributes to global conversations on the balance between legal reform, cultural pluralism, and the protection of civil liberties.